The law applicable to claims for breach of duty of care by foreign controlling companies and their directors under EU law - Mucha, Ariel (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2024)
The research presented in the article aims to identify the criteria for determining the law applicable to third party claims against board members and parent companies for non-contractual obligations. The article examines the provisions of EU law and the case law of the Courts of Justice on the basis of the dogmatic method, combined with elements assessing the economic efficiency of the identified approaches. Research on this topic is prompted by the absence of an adequate legal framework determining the qualification of the claims in question. The Rome II Regulation only provides for the exclusion of company law claims from its scope. However, this exclusion does not provide criteria for determining which claims fall under company law. This issue was recently addressed by the Court of Justice in the case of BMA AG, C-498/20, concerning the scope of the law applicable to the liability of a German company for breach of the general duty of care towards the creditors of a Dutch subsidiary. The Court held that such a claim should be classified as lex delicti. The findings of the research suggest that the Court of Justice has not offered clear criteria that would enable national authorities to distinguish between corporate and tort claims. Meanwhile, it seems that there are more arguments in favour of the corporate nature of claims arising from decisions relating to the management of the company’s assets.